The influence of achievement orientation on player performance: Evidence from Malaysian sport schools. - Nasiruddin, Mohamad Nasrullah; Sin, Ishak; Fauzee, Mohd Sofian Omar (2020)
Achievement orientation influences athlete participation in sports as athletes who have a competitive, goal and winning orientation will be able to adjust before and during the competition to compete to a greater degree. Coaches play an important role in determining the orientation pattern of athlete achievement in order to inculcate high fighting spirit, be positive, and be able to compete further. Therefore, this study was conducted to identify factors that influence the orientation of achievement on player performance in Malaysia. A total of 150 students’ athletes from the Malaysian Sports Schools were selected as respondents of the study. The findings show that all three components of achievement orientation, namely win, competitive and goal are reliable and valid, and the achievement orientation has an impact on player performance. In conclusion, the coach can play a role in improving the player's achievement orientation as well as their performance.